A Contrastive analysis of the syntax of simple English and Tagalog sentences - Jimenez, Richard John Paul B.; Arcellana, Lydia R. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
This study deals with the comparison of two languages namely Tagalog and English. These two languages were compared and contrasted to identify what the differences between these two languages are. By identifying these differences, the difficulties caused by the differences of these two languages that native speakers of Tagalog may encounter when learning the English language may be identified and emphasized when taught and approached in the academe. Using Ian Roberts' X-bar theory, the components of the two equivalent sentences from both English and Tagalog were identified. These components were then graded according to Lado's and Roberts' levels of difficulty. Obviously, those components that are not present in one language but present in another are considered more difficult than components that are both present in the two languages but are signaled differently. (e.g. affixation in English but function word in another.) After grading these components as present in both, present in one and absent in another and similar, the sentence components that exhibited differences were analyzed using Lado's "parallel-inventory style" of language comparisons. This study identified a number of probable points of difficulty that a native speaker of Tagalog might encounter when learning the English language. The verb form "be" the English prepositions and the other English tenses are three of the most difficult English sentence components that Tagalog speakers learning English may encounter since they are not present or have no clear equivalent in the Tagalog language. The English articles and English pronouns are also a bit different from that of Tagalog an should also be considered as probable difficult points to Filipino students learning the English language. The difference in the general structure of both English and Tagalog sentences is another probable difficulty Filipino students might encounter. This is because English sentences usually have verb final structures while Tagalog sentence have verb initial sentence structures. Since this study only deals with the simple sentence types of both English and Tagalog, further studies that tackle more complicated sentence types and structures of English and Tagalog would certainly prove to be beneficial since it would expose and identify more probable points of difficulty Filipino students learning the English language might encounter.
Thesis (B.A. in English Studies : Language)
Includes bibliographical references
Keywords: Tagalog language -- Syntax; English language -- Syntax; Contrastive linguistics